A MODEL PROPOSAL FOR CALCULATING THE THEORETICAL CONGESTION PRICE FOR PRIVATE AUTOMOBILES IN ISTANBUL - Yuksel, Haluk (YILDIZ TECHNICAL UNIV, 2005)
The congestion pricing method is one of the most promising solutions that uses the existing infrastructure, respects the economical and social equity and is environment friendly. for urban transportation problems. One of the most important steps in planning of such an application is calculating the theoretical congestion price with the help of a dynamic model, correctly. In this paper a congestion price calculation model that is developed for use in Turkey, is proposed. The trip time, fuel consumption and fuel emission costs are introduced in the models as costs that vary with the speed of the traffc flow. To serve this purpose a speedflow relation is chosen and calibrated to represent the traffic conditions.
Keywords: Congestion pricing; Urban transportation; Speed-Flow relationship; Engineering